Effects of rumen-protected lysine on antler growth performance, fecal bacterial community, and blood gene expression in sika deer - Yang, Bo; Zhu, Yuhang; Li, Yongxiang; Gao, Yating; Si, Huazhe; Li, Zhipeng (Frontiers in Veterinary Science, 2025)
IntroductionVelvet antler is an important product of sika deer (Cervus nippon), and its growth is closely related to dietary amino acid supplementation. Lysine is one of the major limiting amino acids in animals; however, the mechanism underlying its effect on velvet antler growth in sika deer remains unclear.MethodsThis study investigated the impact of rumen-protected lysine supplementation on velvet antler growth, nutrient digestibility, gut bacteria, serum biochemical parameters, and gene expression in sika deer. Fifteen healthy 2-year-old male sika deer were randomly assigned to three dietary groups: control (0 g/day rumen-protected lysine, CON), low (5 g/day rumen-protected-lysine, LLys), and high (10g/day rumen-protected lysine, HLys).ResultsSupplementation with rumen-protected lysine significantly increased antler weight and dry matter, crude protein, neutral detergent fiber, and acid detergent fiber digestibility (P < 0.05). The concentrations of acetate and propionate in the feces of the LLys were significantly higher than those in the CON (P < 0.05). The relative abundance of Fibrobacter in the feces was significantly higher in the HLys group compared to the CON group (P < 0.05). The relative abundance of Papillibacter, Coprococcus, Anaerorhabdus furcosa, and Parabacteroides were significantly lower in the HLys than in the CON (P < 0.05). The gene expression was influenced in both HLys and LLys groups compared to the CON group, with upregulated dierentially expressed genes (DEGs) and downregulated DEGs identified. KEGG pathway analysis showed upregulated DEGs were enriched in MAPK, PI3K-Akt, TNF, p53, FoxO, JAK-STAT, NF-κB, and Toll like receptor signaling pathways. Down regulated DEGs were enriched in glutathione metabolism, lysine degradation, fatty acid elongation, biosynthesis of unsaturated fatty acids, Th17 and Th2 cell differentiation.ConclusionOverall, these results provide novel insights into the effect of rumen-protected lysine supplementation on antler growth, host digestibility and metabolism, fecal microbiota, and blood transcriptome of sikadeer.